2008
DOI: 10.1111/j.1365-2982.2008.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

The vagus nerve as a modulator of intestinal inflammation

Abstract: The cholinergic nervous system attenuates the production of pro-inflammatory cytokines and inhibits inflammatory processes. Hence, in animal models of intestinal inflammation, such as postoperative ileus and dextran sulfate sodium-induced colitis, vagus nerve stimulation ameliorates disease activity. On the other hand, in infectious models of microbial peritonitis, vagus nerve activation seemingly acts counteractive; it impairs bacterial clearance and increases mortality. It is originally indicated that the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 94 publications
2
90
1
2
Order By: Relevance
“…As a result, the secretion of ACh was reduced and colonic mucosal damage was alleviated through a 'nicotinic anti-inflammatory pathway' dependent on the α7-nicotinic acetylcholine receptor (α7nAChR) [40][41][42] . Our research showed that the discharge frequency of the vagus was decreased after chemical stimulation of the PVN, indicating that the vagus pathway played a critical role in the protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the secretion of ACh was reduced and colonic mucosal damage was alleviated through a 'nicotinic anti-inflammatory pathway' dependent on the α7-nicotinic acetylcholine receptor (α7nAChR) [40][41][42] . Our research showed that the discharge frequency of the vagus was decreased after chemical stimulation of the PVN, indicating that the vagus pathway played a critical role in the protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Hoffman-Goetz et al have found that 16 wk of VWR reduces intestinal lymphocyte production of pro-inflammatory and increases production of anti-inflammatory cytokines in the absence of any inflammatory stimulus . The mechanisms for these anti-inflammatory effects of exercise in the gut are unknown, but may involve activation of the parasympathetic cholinergic anti-inflammatory reflex (Van Der Zanden et al, 2009). In some instances (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is also intense recent work investigating the role that VNS might have on inflammation and the immune response (Ottani et al, 2009;Pavlov, 2008;Van Der Zanden et al, 2009). …”
Section: Research Usesmentioning
confidence: 99%